The fat cover in gilts in relation to body condition and reproduction - Václav Matoušek; N. Kernerová; L. Máchal; J. Václavovský (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2011)
A study was conducted in a set of hybrid gilts of F1 generation of Czech Large White x Czech Landrace breeds coming from a multiplication herd. The objective of the study was to test a possibility of using the measured traits, i.e. backfat thickness (BT) and lean meat content (LM), for objective determination of changes in the body condition score of gilts during rearing and in relation to their subsequent fertility in parities 1. At the ultrasonic measurement in the multiplication herd the purchased gilts showed the average daily gain (ADG) from birth 612.5 g, average backfat thickness (ABT) 8.34 mm, loin muscle depth (LMD) 48.83 mm and LM 62.26%. At the first determination of own performance traits in a production herd the values of ABT, LMD and LM were 13.26 mm, D 59.29 mm and 58.83%, respectively. In a subsequent measurement (at the onset of standing heat) the respective values of ABT, LMD and LM were 15.15 mm, 62.31 mm and 57.42%. Correlation coefficients for the measured traits of own performance in relation to reproductive traits in parities 1 were mostly low, statistically insignificant.